Protection offered by COVID-19 vaccine against morbidity and mortality due to COVID-19 infection: a postvaccination cohort study - Muley, Arti; Mitra, Sona; Bavishi, Ashish; Bhojani, Hema; Patel, Geetika; Nakum, Dinesh; Shah, Sakshi; Prajapati, Pratham; Abraham, Ayush; Patel, Parth; Patel, Mit; Padia, Stavan; et al. (International Journal of Advances in Medicine, 2021)
Background: Many vaccines have been developed, approved and administered against the COVID-19. Phase 2 and 3 trials have proved the safety and tolerability of these. This study was conducted to assess effect of the vaccines on morbidity and mortality due to postvaccination new COVID-19 infection. Methods: This was an observational, retrospective cohort study. The patients admitted with COVID-19 from 1st April 2021 till 30th April 2021 who were willing to participate were included. All the patients were telephonically contacted post discharge and enquired regarding history of vaccination, events during hospitalization and outcome. The data so collected was analysed to compare the morbidity (oxygen requirement, need of ICU admission and need of BiPAP or invasive ventilation) and mortality between vaccinated and nonvaccinated COVID-19 patients and relation of time elapsed post vaccination with morbidity and mortality. Results: Total 431 patients were included. There was significant difference between the two groups in terms of need for ICU admission (OR 0.503; CI 0.30-0.82, p=0.008) as well as requirement of BiPAP or invasive ventilation (OR 0.57; CI 0.33-0.98, p=0.05). Mortality was significantly less in the vaccinated group; OR 0.48 (0.24-0.95), p=0.04). Ten patients had received both doses. Only one required ICU while none of them required invasive ventilation and none expired. Conclusions: COVID-19 vaccine gives significant protection against COVID-19 infection related ICU admission, need of mechanical ventilation and mortality even after single dose. Two doses of vaccine may afford better protection against the disease.